KEKERASAN DALAM MEDIA MASSA SEBAGAI CONTOH BENTUK PENDIDIKAN DISKRIMINATIF TERHADAP PEREMPUAN - mu’awanah, M.Pd, Hj. Elfi (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2008)
Violence on mass media is one short of discrimination towards women. It shows the fact that violence which are mostly women experiencing needs real solution such as gender issues and regulation on domestic violence socialization. Government plays important part in reducing the rate of domestic violence that are presented in mass media lately in terms of law enforcement. It is also crucial that all people are aware of this issue if they become the victims report to institution or person who is in charge with domestic violence case.